RANCANG BANGUN SISTEM PENGELOLAHAN DATA SISWA MI HASYIM ASY’ARI BERBASIS WEBSITE - Mohammad Baidhowi Alwi; Tri Deviasari Wulan; Endang Sulistiyani (Universitas Nahdlatul Ulama Surabaya, 2020)
Abstract: The very rapid development of information and communication technology has now become a demand in the world of education to always adjust technological developments to efforts to improve the quality of education. In this study, researchers will create a student data management information system at MI Hasyim Asy'ari. This is because the existing system performance in MI Hasyim Asy'ari is currently still running slowly for processing student data and registering new students. The method used in this research is the SDLC (System Development Life Cycle) method approach, this method is a basic method in making information systems starting from business process modeling, system analysis has new system requirements, namely functional requirements including online student registration, value input. students, making selection announcements, active student registration, online transfer and alumni, online student data search and data backup using databases and non- functional including laptop or computer hardware, wifi and domain software, hosting and browser, system design , system creation and testing which consists of 2 methods, namely blackbox testing and user acceptance testing where all the test results are successful and the user finds it easy to use them, for programming using PHP and MySql languages with a codeigniter framework. The result of this research is the MI Hasyim Asy'ari Student Data Processing Information System.